First-trimester ultrasound measurements and maternal serum biomarkers as prognostic factors in monochorionic twins: a cohort study - Fiona L. Mackie; Rebecca Whittle; R. Katie Morris; Jon Hyett; Richard D. Riley; Mark D. Kilby (Diagnostic and Prognostic Research, 2019)
Abstract Background Monochorionic twin pregnancies are at high risk of adverse outcomes, but it is not possible to predict which pregnancies will develop complications. The aim of the study was to evaluate, in monochorionic twin pregnancies, whether first-trimester ultrasound (nuchal translucency [NT], crown-rump length [CRL]), and maternal serum biomarkers (alpha-fetoprotein [AFP], soluble fms-like tyrosine kinase-1 [sFlt-1] and placental growth factor [PlGF]), are prognostic factors for fetal adverse outcome composite, twin-twin transfusion syndrome (TTTS), growth restriction, and intrauterine fetal death (IUFD). Methods A cohort study of 177 monochorionic diamniotic twin pregnancies. Independent prognostic ability of each factor was assessed by multivariable logistic regression, adjusting for standard prognostic factors. Factors were analysed as continuous data; thus, the reported ORs relate to either 1% change in NT or CRL inter-twin percentage discordance or one unit of measure in each serum biomarker. Results The odds of the fetal adverse outcome composite were significantly associated with increased NT inter-twin percentage discordance (adjusted OR 1.03 [95% CI 1.01, 1.06]) and CRL inter-twin percentage discordance (adjusted OR 1.17 [95% CI 1.07, 1.29]). TTTS was significantly associated with increased NT discordance (adjusted OR 1.06 [95% CI 1.03, 1.10]) and decreased PlGF (adjusted OR 0.42 [95% CI 0.19, 0.93]). Antenatal growth restriction was significantly associated with increased CRL discordance (adjusted OR 1.20 [95% CI 1.08, 1.34]). Single and double IUFD were associated with decreased PlGF (adjusted OR 0.34 [95% CI 0.12, 0.98]) and (adjusted OR 0.18 [95%CI 0.05, 0.58]) respectively. Conclusion(s) This study has identified potential individual prognostic factors in the first trimester (fetal biometric and maternal serum biomarkers) that show promise but require further robust evaluation in a larger, prospective series of MC twin pregnancies, so that their usefulness both individually and in combination can be defined. Trial registration ISRCTN 13114861 (retrospectively registered)